Ethnomathematics Exploration of Making Traditional Ombus-ombus Cake Typical of North Tapanuli as a Source of Mathematics Learning - Hasibuan, Havidah Adawiyah; Irvan, Irvan (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
There has been a lot of research on ethnomathematics regarding ombusombus cake, but no one has studied their mathematical value from all aspects of the material other than 2D shapes or 3D shapes. This research aims o look for mathematical activities in North Tapanuli culture and focused on developing the ethnomathematics value of the traditional ombusombus food cake typical of North Tapanuli as a source of mathematics learning. The basic ingredient for making ombus-ombus is rice flour. This research is descriptive qualitative research with an ethnographic approach. Data collection techniques were carried out using observation, documentation, and literature review.  Data analysis techniques using Spradley design: domain analysis, taxonomy, compatibility, and cultural themes. Based on the results of data collection, there were several mathematical elements in the traditional ombus-ombus cake typical of North Tapanuli. The mathematical elements contained include the concept of comparison, flat shapes (triangles and squares), space shapes (quadrangular pyramids), social arithmetic concepts, measurement concepts, and counting concepts. In this way, Ombus-ombus can be used as a medium for teaching mathematics in the classroom.